THE INFLUENCE OF TRADITIONAL EASTERN CULTURAL VALUES AND MODERN WESTERN SOCIAL MODELS ON THE MINDS OF YOUNG PEOPLE - Umarov Khumoyunmirzo Zakhriddinbobur Ogli (International Scientific and Current Research Conferences, 2025)
In the context of increasing globalization and cultural convergence, this article explores the multifaceted influences of Eastern traditional cultural values and Western modern social models on the formation of youth identity, behavior, and worldview. It critically examines how Eastern philosophical and ethical systems—rooted in Confucianism, Islamic heritage, collectivism, and respect for authority—continue to shape youth moral development and social cohesion, particularly in Asian and Muslim-majority societies. Simultaneously, the article investigates the pervasive influence of Western social models characterized by individualism, liberalism, technological determinism, and consumerist culture, and how these paradigms are reshaping youth aspirations, cultural affiliations, and life trajectories. Through a comparative cultural analysis supported by empirical studies and sociological data, the study aims to highlight the complex interplay, contradictions, and potential harmonization between traditional Eastern values and modern Western influences. The article concludes with policy-oriented recommendations for education and youth development programs that balance cultural preservation with global adaptability.